Antibacterial activity and modes of action of phosvitin-derived peptide Pt5e against clinical multi-drug resistance bacteria. (November 2016) - Li, Zhijian; Wang, Peng; Jiang, Chengyan; Cui, Pengfei; Zhang, Shicui
Abstract: Pt5e, a mutant peptide derived from the C-terminal 55 residues of zebrafish phosvitin, has been suggested to be a novel antibacterial peptide. However, if it is applicable to clinical MDR bacteria remains to be tested. In this study, high-purity Pt5e was first expressed and purified by fusion with cationic elastin-like polypeptide. Pt5e was then shown to be capable of effectively killing all the five clinical MDR bacteria tested. Pt5e kill the MDR bacteria at several levels, including inserting into the bacterial membranes, causing the membrane depolarization and permeabilization, and inducing the intracellular apoptosis/necrosis. All these data suggest that Pt5e is a promising therapeutic potential as an antibiotics against clinical MDR bacteria. Highlights: High-purity Pt5e is expressed and purified by fusion with CELP. Pt5e is capable of killing all the five clinical MDR bacteria tested. Pt5e is able to deposit onto the bacterial membranes. Pt5e induces membrane permeabilization/depolarization and apoptosis/necrosis.